2015
DOI: 10.1016/j.jconrel.2015.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Remote spatiotemporally controlled and biologically selective permeabilization of blood-brain barrier

Abstract: The blood-brain barrier (BBB), comprised of brain endothelial cells with tight junctions (TJ) between them, regulates the extravasation of molecules and cells into and out of the central nervous system (CNS). Overcoming the difficulty of delivering therapeutic agents to specific regions of the brain presents a major challenge to treatment of a broad range of brain disorders. Current strategies for BBB opening are invasive, not specific, and lack precise control over the site and timing of BBB opening, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Therefore, significant efforts are being made to design safe and sophisticated strategies to bypass such barriers for efficient drug delivery (1417). Multiple recent studies have shown that exposure to external beam radiation enhances BTB permeability in mice bearing orthotopic GBMs (1822).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, significant efforts are being made to design safe and sophisticated strategies to bypass such barriers for efficient drug delivery (1417). Multiple recent studies have shown that exposure to external beam radiation enhances BTB permeability in mice bearing orthotopic GBMs (1822).…”
Section: Introductionmentioning
confidence: 99%
“…These disadvantages may limit their clinical translation. A novel approach has been described based on a combination of stromal cell delivery, heat-inducible gene expression, and mild heating with high-intensity focused ultrasound (HIFU) under MRI guidance to remotely permeabilize the BBB [148] . The principle of this method is to administrate stromal cells engineered to express pro-inflammatory factors that will permeabilize the BBB but only trigger their expression after heating with non-invasive imageguided HIFU.…”
Section: Methods To Promote the Homing Of Mscs In The Treatment Of Cnmentioning
confidence: 99%
“…The biologic targeting of stem cells along with the spatial targeting of HIFU can be combined to create a remote-controlled expression platform has been leveraged to assist in locally opening up the BBB for facilitated drug delivery of systemically administered agents (41). This can be accomplished by remotely triggering expression of effector cytokines, such as TNFα, from engineered tumorhoming stem cells in response to noninvasive image-guided HIFU ( Figure 1C).…”
Section: Controllable Drug Delivery Using Stem Cells In Conjunction Wmentioning
confidence: 99%
“…By combining stem cell delivery, heat-inducible gene expression and mild heating with HIFU, Xiong et al demonstrated that HIFU can be used to remotely control the expression of pro-inflammatory factors engineered in stem cells under the control of the HSP70 promoter ( Figure 1C). This targeted expression led to the permeabilization of the BBB with highspatiotemporal precision and biologic selectivity, allowing for penetration of systemically administered small molecular MRI contrast agent and 300-nm-sized nanoparticles into the brain ( Figure 1D, E) (41). This opening of the BBB was limited to where selected factors were secreted secondary to HIFU activation, near the engineered stem cells and consequently the infiltrating tumor cells.…”
Section: Controllable Drug Delivery Using Stem Cells In Conjunction Wmentioning
confidence: 99%
See 1 more Smart Citation